ANNUAL EFFECTIVE DOSE ESTIMATION DUE TO THE NATURAL RADIOACTIVITY IN YAM TUBERS (Dioscorea rotundata) CULTIVATED IN NORTHCENTRAL NIGERIA - Matthew Tikpangi Kolo; Oyeleke Ismail Olarinoye; Simon Olonkwoh Salihu; Hauwau Kulu Shuaibu; Funmilayo Ayedun (Malaysian Journal of Science, 2023)
Yam tubers (Dioscorea rotundata) and soil from commercially cultivated farmland in northcentral Nigeria were collected and investigated for their natural radioactivity content using a 3” × 3” NaI(Tl) gamma detector. Average activities of 238U, 232Th and 40K in the investigated farm soil were 38.13±3.76 Bq kg-1, 15.06±0.99 Bq kg-1 and 381.80±15.50 Bq kg-1, respectively. The results agree with the world’s acceptable levels of safety. Activities measured in the yam tubers were in the range from BDL -76.68±9.73 Bq kg-1 for 238U, BDL - 19.77±1.30 Bq kg-1 for 232Th and 312.50±20.73 - 627.94±38.37 Bq kg-1 for 40K, with average values of 29.23±4.0, 13.10±0.72 and 445.10±27.20 Bq kg-1, respectively. The total effective dose from radionuclide intake from yam ingestion fluctuated between 272.12 μSv y-1 and 935.97 μSv y-1. Correlation analysis identified 238U and 232Th as the leading contributors to the total effective dose from ingesting yam tubers cultivated in northcentral Nigeria.